2004
DOI: 10.2134/agronj2004.0135
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Leaf Nitrogen Status in Rice with Canopy Spectral Reflectance

Abstract: instantaneous results and has been demonstrated as an effective tool to schedule N fertilization for rice (Oryza Nondestructive monitoring and diagnosis of plant N status is necsativa L.) on an as-needed basis (Turner and Jund, 1991; essary for precision N management. The present study was conducted to determine if canopy reflectance could be used to evaluate leaf Peng et al., 1993). However, there are two factors that N status in rice (Oryza sativa L.). Ground-based canopy spectral limit the use of SPAD me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(113 citation statements)
references
References 27 publications
4
106
3
Order By: Relevance
“…Aparicio et al 2000;Ma et al 2001) and nutritional status of crops (e.g. Filella et al 1995;Graeff and Claupein 2003;Xue et al 2004).…”
Section: Breeding For Dehydration Avoidancementioning
confidence: 99%
“…Aparicio et al 2000;Ma et al 2001) and nutritional status of crops (e.g. Filella et al 1995;Graeff and Claupein 2003;Xue et al 2004).…”
Section: Breeding For Dehydration Avoidancementioning
confidence: 99%
“…Stone et al demonstrated a high correlation between plant N spectral index (PNSI), the reciprocal of Normalized Difference Vegetation Index (NDVI), and total N uptake of wheat [11]. The feasibility of field evaluation for crop N status using canopy reflectance spectra has also been tested [12,13]. These reports showed that remote sensors were reliable in estimating plant N status.…”
Section: Introductionmentioning
confidence: 99%
“…Inoue et al (1998) examined the relationship between N fertilizer applications and reflectance spectra in field corn and found that vegetation indices of R1100 and R660 had the highest correlations with N application, where NDVI is calculated as (R1100 -R660)/ (R1100 + R660). Furthermore, Xue et al (2004) determined that the reflectance ratio of 810 nm to 560 nm (R810/R560) is linearly related to leaf N concentration. In the current study, reflectance indices were useful to measure leaf N concentration in P. lanceolata when developing indices for non-destructive Chl estimation, and NDVI was used to assess Chl content and photosynthetic capacity.…”
Section: Discussionmentioning
confidence: 99%